2019
DOI: 10.1002/adfm.201907572
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Origin of Cancer‐Mobile Quantum Probe for Single Cancer Stem Cell Detection

Abstract: Cancer stem cells (CSC) are believed to be the driving force of cancer metastases and are a rare population of self‐renewing cells that contribute majorly to the poor outcomes of cancer therapy. The detection of CSC is of utmost importance to shed light on the indestructible nature of certain solid tumors and their metastatic ability. However, tumors tend to harbor CSCs in a specialized niche, making the detection process difficult. Currently, there is no method available to detect CSCs. The significance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…The results were then compared with SERS data. The characteristic Raman peak of CD44 was obtained from the literature (829 cm –1 ) . Intensity at the peak was calculated for CSCs and results were compared with the intensity of the peak for cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were then compared with SERS data. The characteristic Raman peak of CD44 was obtained from the literature (829 cm –1 ) . Intensity at the peak was calculated for CSCs and results were compared with the intensity of the peak for cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic Raman peak of CD44 was obtained from the literature (829 cm −1 ). 15 Intensity at the peak was calculated for CSCs and results were compared with the intensity of the peak for cancer cells. As shown in Supporting Figure 7A, the fluorescence images of cervical CSC as well as breast CSC demonstrated very high expression of CD44 as compared to the respective cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the top of the tumor hierarchy are CSCs, which are responsible for the initiation, progression, drug resistance, and recurrence of metastasis. CSCs have demonstrated a capacity for self-renewal and treatment resistance, and very few CSCs can generate tumors of heterogeneous cancer cells making CSCs important targets for cancer diagnosis and therapy. However, complete profiling of CSCs has been challenging due to their rarity, unique features, and quiescent state with slow-growth properties. ,, The communication pathways for CSCs identified so far are mostly shared with either cancer cells or stem cells. , As existing CSC research is mostly focused on irregularities in the homeostasis controlling pathways, epigenetics, and CSC metabolism, CSC-specific universal markers for cancer subtype are not available . As per our current understanding of CSCs, there is no consensus on CSC-specific surface markers yet. , It is impossible to target CSCs based on a single molecular marker or single pathway because of the plasticity of CSCs to gain or lose CSC features .…”
Section: Introductionmentioning
confidence: 99%
“…The SERS technique has thus been exploited in diverse analytical applications. Given that the real part of the dielectric constant must be negative and the ratio of the positive and negative parts must be large for a frequency-dependent complex permittivity to induce the LSPR phenomena, noble metals have typically been used to create the SERS substrate . Based on developments over the last 40 years, SERS has proved to be a versatile analytical tool for trace detection, bioimaging, disease diagnosis, and food security testing. Currently, the development efforts on SERS are focused mainly on (1) applying nanosensors for multidisciplinary research , and (2) achieving higher SERS enhancement factors (EFs) through sophisticated fabrication of nanostructures with tailored designs. With respect to the EF, experimental studies have been performed regarding the hot spot involving the collective excitations at the nanogap formed in metal structures, where single molecule SERS (SM-SERS) detection is expected to be realized. From theoretical considerations, it is recognized that the SERS enhancement effect is equal to the fourth power of the local field ( E max / E 0 ) based on a first-order approximation of the electromagnetic mechanism, which suggests that the SERS EF will be higher than 10 12 to realize SM-SERS. However, for detection of label-free molecules at a very low concentration (<1 nM), it has been demonstrated that SM-SERS is exceptionally difficult to realize because of the so-called blinking SERS phenomenon. , The blinking SERS causes strong fluctuations in the SERS signals, thus hindering the collection of reliable statistics for SERS signals . In brief, it has been speculated that blinking SERS may be due to the migration of a label-free single molecule out of the hot spot, resulting in a reduction of the LSPR .…”
Section: Introductionmentioning
confidence: 99%